2008
DOI: 10.1007/s11920-008-0026-1
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia and 22q11.2 deletion syndrome

Abstract: Abstract22q11.2 deletion syndrome (22qDS) is a genetic syndrome associated with a chromosome 22q11.2 deletion and variable phenotypic expression that commonly includes schizophrenia. Approximately 1% of patients with schizophrenia have 22qDS. The schizophrenia in 22qDS appears broadly similar to that found in the general population with respect to core signs and symptoms, treatment response, neurocognitive profile, and MRI brain anomalies. However, individuals with a 22qDS form of schizophrenia typically have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
166
3
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 212 publications
(184 citation statements)
references
References 50 publications
4
166
3
6
Order By: Relevance
“…These included discussion regarding the early warning signs and treatment of psychiatric illnesses. This was consistent with literature suggesting that individuals with 22q11.2DS should be followed for early signs of psychotic illness because early diagnosis and effective treatment for schizophrenia can lead to a better prognosis and improved functioning (Bassett and Chow 2008;Bassett et al 2011;Hodgkinson et al 2001). A pilot study reported that genetic counselors felt unprepared to raise the issue of psychiatric illness with patients or to answer questions regarding psychiatric illness due to their lack of understanding of a psychiatric diagnosis and their knowledge about issues involved in psychiatric genetics (Peay and McInerney 2002).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These included discussion regarding the early warning signs and treatment of psychiatric illnesses. This was consistent with literature suggesting that individuals with 22q11.2DS should be followed for early signs of psychotic illness because early diagnosis and effective treatment for schizophrenia can lead to a better prognosis and improved functioning (Bassett and Chow 2008;Bassett et al 2011;Hodgkinson et al 2001). A pilot study reported that genetic counselors felt unprepared to raise the issue of psychiatric illness with patients or to answer questions regarding psychiatric illness due to their lack of understanding of a psychiatric diagnosis and their knowledge about issues involved in psychiatric genetics (Peay and McInerney 2002).…”
Section: Discussionsupporting
confidence: 92%
“…Providing information regarding changes in behavior, thinking, emotions and/or sleep, energy level or appetite that should prompt psychiatric assessment as well as the treatable nature of psychiatric illness would not only help parents but may also help to reduce genetic counselors' discomfort in discussing the increased prevalence of psychiatric illness in 22q11.2DS Chow 2008, Bassett et al 2008a). Notably, there are no clinical tests or individual features, including childhood conditions such as attention deficit or learning difficulties, that are useful for predicting later onset of psychotic illness, although there is much research interest in this area for 22q11.2DS (Bassett and Chow 2008;Philip and Bassett 2011). In the context of reassurance about the inability to predict or control the future, it may be helpful to discuss general factors that may help with resilience to both the stress of daily living (Feder et al 2009) and the chronic and acute adversity faced by individuals with 22q11.2DS.…”
Section: Discussionmentioning
confidence: 99%
“…Krahn's patient, however, presented very differently from ours and we believe antipsychotic medications may have played a significant role. Although there is little published data, neurologic, including parkinsonian, side effects of antipsychotic medications may be common in 22qDS [Bassett and Chow, 2008]. Lynch et al [1995] reported a young adult with 22qDS and a neurodegenerative disorder with ataxia and parkinsonian features, including bradykinesia.…”
Section: Patient 2: This 56-year-old Man Presented To the Clinical Gementioning
confidence: 99%
“…Interestingly, only one patient manifested psychotic symptoms before PD, conversely to the high frequency of schizophrenia (about 30%) reported in literature [5].…”
Section: R E V I S E D M a N U S C R I P Tmentioning
confidence: 49%
“…The 22q11.2DS, usually diagnosed in children, is exceptionally diagnosed in adults where it usually manifests as a long history of psychiatric disorders such as schizophrenia [4,5]. Some authors first reported co-occurrences of early onset Parkinson disease (EOPD) and 22q11.2DS [4,[6][7][8] and searched for any molecular links [6,9].…”
Section: Introductionmentioning
confidence: 99%